2019
DOI: 10.2147/imcrj.s206596
|View full text |Cite
|
Sign up to set email alerts
|

<p>Unilateral Proptosis As An Initial Sign Of Acute Myeloid Leukemia In A Child: A Case Report</p>

Abstract: Granulocytic sarcoma (chloroma) is a rare malignant solid tumor representing an extramedullary manifestation of acute myeloid leukemia (AML). Rarely, a chloroma can develop as the sole manifestation and its appearance may precede the systemic manifestations of acute myelocytic leukemia by months to years. We report a rare case of unilateral orbital mass presenting with progressive proptosis involving left globe in an otherwise healthy child, and give a brief overview of the literature about this unusual presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…15 The common characteristics of orbital MS were proptosis, chemosis, orbital mass, and lid edema. 14 , 16 , 17 Ocular MS in adult AML patients was 10 out of 3,724 (0.3%) in the study, 17 whereas Cavdar et al reported 33 orbito-ocular MS in 133 Turkish children with AML. 18 The Children’s Oncology Group concluded that patients with MS involving orbital and central nervous system (CNS) sites had significantly better survival than patients with non-CNS MS, with CSF leukemia, or without extramedullary leukemia.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…15 The common characteristics of orbital MS were proptosis, chemosis, orbital mass, and lid edema. 14 , 16 , 17 Ocular MS in adult AML patients was 10 out of 3,724 (0.3%) in the study, 17 whereas Cavdar et al reported 33 orbito-ocular MS in 133 Turkish children with AML. 18 The Children’s Oncology Group concluded that patients with MS involving orbital and central nervous system (CNS) sites had significantly better survival than patients with non-CNS MS, with CSF leukemia, or without extramedullary leukemia.…”
Section: Discussionmentioning
confidence: 65%
“…Myeloid sarcoma (MS) of orbit, presenting as malignant myeloid precursor cells invading orbital soft tissue, 13 might be the first manifestation of AML 14 or signify a relapse. It often involves bones and extends into the orbital fossa.…”
Section: Discussionmentioning
confidence: 99%
“…Chefchaouni reported that 2% of children treated for leukemia suffered from proptosis [ 8 ]. Almaki et al [ 9 ] also reported a case of unilateral proptosis in a previously healthy child as an initial sign of acute myeloid leukemia. Such conditions should be considered in the absence of systemic leukemic manifestations as the form of granulocytic sarcoma (chloroma) [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…Almaki et al [ 9 ] also reported a case of unilateral proptosis in a previously healthy child as an initial sign of acute myeloid leukemia. Such conditions should be considered in the absence of systemic leukemic manifestations as the form of granulocytic sarcoma (chloroma) [ 9 ]. However, our patient showed bilateral proptosis, which is a unique case of acute myeloid leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…and form soft tissue masses. 4 The direct infiltration of the orbits in leukemia can result in proptosis, chemosis, diplopia, lid edema, blurring of vision, palsies of the extra-ocular muscle, intra-retinal macular or sub-hyaloid hemorrhages, cotton wool spots, or papilledema due to the increased intracranial pressure. 5 Proptosis is the most common presentation of orbital MS. 3 Isolated unilateral proptosis as initial presentation of AML has been reported, wherein the bone marrow was positive for leukemic cells.…”
Section: Case Reportmentioning
confidence: 99%